Synthetic Lethal Activity of Benzophenanthridine Alkaloids From Zanthoxylum coco Against BRCA1-Deficient Cancer Cells - García, Iris A.; Pansa, Maria Florencia; Pacciaroni, Adriana Del Valle; García, Manuela E.; Gonzalez, Maria Laura; Oberti, Juan Carlos; Bocco, José Luís; Carpinella, Maria Cecilia; Barboza, Gloria E.; Nicotra, Viviana E.; Soria, Gastón (Frontiers in Pharmacology, 2020)
Several plants from South America show strong antitumoral properties based on anti-proliferative and/or pro-apoptotic activities. In this work we aimed to identify selective cytotoxic compounds that target BRCA1-deficient cancer cells by Synthetic Lethality (SL) induction. Using a high-throughput screening technology developed in our Lab, we analyzed a collection of extracts from 46 native plant species from Argentina using a wide dose-response scheme. A highly selective SL-induction capacity was found in an alkaloidal extract from Zhanthoxylum coco (Fam. Rutaceae). Bio-guided fractionation coupled to HPLC led to the identification of active benzophenanthridine alkaloids. The most potent SL activity was found with the compound oxynitidine, which showed a remarkably low relative abundance in the active fractions. Further validation experiments were performed using the commercially available and closely related analog nitidine, which showed SL-induction activity against various BRCA1-deficient cell lines with different genetic backgrounds, even in the nanomolar range. Exploration of the underlying mechanism of action using BRCA1-KO cells revealed AKT and topoisomerases as the potential targets responsible of nitidine-triggered SL-induction. Taken together, our findings expose an unforeseen therapeutic activity of alkaloids from Zhanthoxylum-spp. that position them as novel lead molecules for drug discovery.